Service users’ perceptions of relevant and helpful components of an integrated care concept (ACCESS) for psychosis - Rohenkohl, Anja Christine; Sowada, Pia; Lambert, Martin; Gallinat, Jürgen; Karow, Anne; Lüdecke, Daniel; Rühl, Friederike; Schöttle, Daniel (Frontiers in Psychology, 2023)
Introduction: Psychotic disorders have a significant impact on patients' lives and their families, and long-term treatment with individually tailored multimodal combinations of therapies is often required. Integrated care (IC) concepts such as the "Hamburg Model (ACCESS)" with a focus on psychotic disorders, includes different (therapeutic) components with pharmacoand psychotherapy, family involvement, home treatment and the option of using a 24/7 crisis hotline. All components are offered by a therapeutically-oriented assertive community treatment (TACT) team in a need-adapted manner. So far, however, little is known about which specific components are regarded as especially relevant and helpful by the users of IC. Methods: Patients currently participating in IC completed a questionnaire as part of the continuous quality assurance study (ACCESS II) in which they were asked to rate the different components of treatment according to their relevance and helpfulness, considering the individual's unique experiences with IC and needs in mental health care. Furthermore, they were asked to make suggestions regarding additional helpful components of treatment. Results: Fifty patients participated in this survey (23% of the patients currently participating in the IC concept). For participants, the most helpful and important factors were having the same therapist in the long-term and the 24/7 crisis telephone. Additional components suggested by patients included more addiction-specific therapies and increased focus on vocational rehabilitation and integration.From the perspective of the users of IC, long-term care from a trusted therapist with whom there is a therapeutic relationship and the possibility to reach someone they already know from the TACT team 24/7 serves as the best basis for effective care, fostering trust, understanding, and open communication. In contrast, home treatment remains a relevant aspect of evidence-based care for people with severe mental illness, but perhaps surprisingly, is not viewed as the most important issue.